Intraosseous meningioma mimicking osteosarcoma - Ruben Delgado; Hisham F. Bahmad; Vinay Bhatia; Allen B. Kantrowitz; Cristina Vincentelli (University of São Paulo, 2021)
Background: Predominantly intraosseous meningiomas are rare entities that include true primary intraosseous meningiomas (PIM), as well as meningiomas that may show extensive bone involvement, such as en plaque meningiomas. Different hypotheses have been proposed to decipher the origin of PIMs, such as ectopic arachnoid cap cell entrapment during birth or after trauma. Surgical resection is the treatment of choice of such lesions. Case presentation: We present a case of a 65-year-old man with an enlarging mass in the parieto-occipital region that grew slowly and progressively over 13 years, following head trauma during a motor vehicle accident. One year prior to presentation, he started experiencing daily holocranial headaches and blurry vision. CT and MRI studies revealed a permeative midline calvarial lesion measuring 14 cm in greatest dimension with extensive periosteal reaction, extension into the subcutaneous soft tissues, subjacent dural thickening and intracranial extension with invasion of the superior sagittal sinus. The favored pre-operative clinical diagnosis was osteosarcoma. The abnormal calvarium was excised and histopathological examination confirmed the diagnosis of a predominantly intraosseous calvarial meningioma, WHO grade I. Conclusions: The present case highlights the importance of histopathologic diagnosis in guiding therapeutic decisions and reiterates the necessity of considering PIM or meningiomas with extensive intraosseous component in the differential diagnosis of calvarial masses, even when imaging suggests a neoplasm with aggressive behavior, such as osteosarcoma.